Primary Fibrosarcoma of the Testis and Other Scrotal Contents: A Review and Update - Kodzo-Grey Venyo , Anthony (International Research in Medical and Health Sciences, 2019)
Primary fibrosarcoma of the scrotal contents has been sporadically reported with short-term and medium-term follow-up data. Generally, the tumours had presented insidiously as slow-growing intra-scrotal masses and some of them had presented as a recent increase in the size of a long-standing scrotal masses. The results of serum beta-human chorionic gonadotrophin, alpha-fetoprotein, and lactate dehydrogenase tend to be normal. Radiology imaging of the scrotal masses tended to show a heterogeneous mass within the testis or localized a specific site in the scrotum displacing the ipsilateral testis to the contralateral side. The tumours have generally been treated by means of radical orchidectomy (radical excision of tumour with tumour-free surgical excision margin) alone but some individuals have undergone adjuvant radiotherapy alone plus or minus adjuvant chemotherapy. Diagnosis is based upon the histopathology and the immunohistochemistry examination features of the tumour. The long-term survival rates of patients who have been treated for fibrosarcoma tend to be low despite radical excision, radiotherapy, and chemotherapy. Tumours that are large-sized, poorly differentiated as well as tumours that have high mitotic figures tend to have an inferior prognosis. Radiotherapy-induced fibrosarcoma of the inguinoscrotal content has been reported pursuant to radical orchidectomy plus adjuvant radiotherapy for seminoma of the testis which would indicate that perhaps radiotherapy should not be used. There is a need to identify though a meticulous research specific combination chemotherapy medicaments that would effectively destroy fibrosarcoma tumour cells at the initial stage of treatment. The possibility of the use of immunotherapy as additional treatment should be investigated through a multi-centre global study so that patients, who have intra scrotal fibrosarcomas that are large-sized, poorly differentiated and that contain high mitotic activity could be treated with neoadjuvant chemotherapy followed by radical orchidectomy and adjuvant chemotherapy plus or minus immunotherapy in order to improve the long-term survival.